Antioxidant, Anticancer, and PXR-Dependent CYP3A4 Attributes of Schweinfurthia papilionacea (Burm.f.) Boiss., Tricholepis glaberrima DC. and Viola stocksii Boiss. (16th February 2022) - Shahbaz, Amir; Iqbal, Javed; Abbasi, Banzeer Ahsan; Akhtar, Wasim; Fatima, Iram; Zahra, Syeda Anber; Kanwal, Sobia; Sharifi-Rad, Javad; Sher, Hassan; Mahmood, Tariq; Cho, William C.
Abstract : Present study established the biological potential of Schweinfurthia papilionacea, Tricholepis glaberrima and Viola stocksii extracts for their potential applications in drug formulations. Initially, FTIR was performed to ascertain functional groups and then plant extracts were prepared using five solvents depending on the polarity. Total phenolic contents were observed in the range of 36.36 ± 1.08 mg GAE/g to 95.55 ± 2.46 mg GAE/g while flavonoid contents were found in the range of 10.51 ± 0.25 mg QE/g to 22.17 ± 1.79 mg QE/g. Antioxidant activity was determined using TRP, CUPRAC, TAC and DPPH assays and was recorded highest in S. papilionacea followed by T. glaberrima extracts. TPC and TFC were found to be strongly correlated with TRP (r > 0.50), CUPRAC (r > 0.53) and DPPH (r = 0.31 and 0.72) assay while weakly correlated with TAC (r = 0.08 and 0.03) as determined by Pearson correlation analysis. Anticancer activity showed that S. papilionacea chloroform extracts possess highest cell viability (85.04 ± 4.24%) against HepG2 cell lines while T. glaberrima chloroform extracts exhibited highest activity (82.80 ± 2.68%) against HT144 cell lines. Afterwards, highest PXR activation was observed in T. glaberrima (3.49 ± 0.34 μ g/mL fold) at 60 μ g/mL and was correlated with increase in CYP3 A4 activity (15.0 ± 3.00 μ g/mL IC50 value). Furthermore, antimalarial activity revealed >47600 IC50 value against P. falciparum D6 and P. falciparum W2 and antimicrobial assay indicated highest activity (32 ± 2.80 mm) in S. papilionacea against C. neoformans . At the end, GC-MS analysis of n-hexane plant extracts showed 99.104% of total identified compounds in T. glaberrima and 94.31% in V. stocksii . In conclusion, present study provides insight about the different biological potentials of S. papilionacea and T. glaberrima extracts that rationalize the applications of these extracts in functional foods and herbal drugs for the management of oxidative-stress related diseases, antimicrobial infections and liver and skin cancer.